Land Suitability System of Food Crops using Quick Basic - . Santosa (Jurnal Keteknikan Pertanian, 2000)
Ihe research was done to design computer sojiware for land suitability identification offood crops, i.e.: wetland rice, upland rice, maize, soybean, phaseolus bean, sweet potato, cassava, white potato, and cocoyam/taro using Quick BASIC.After having user input the data of certain physical characteristics of the land, the system examined the program and then the system was capable to give the rank of the crops with certain score. The crop with the biggest score is the most suitable crop for that land.